The adventures of Don Quixote - Cervantes Saavedra, Miguel de, 1547-1616.; Cohen, J. M. (John Michael), 1903-1989. (Maryland : Penguin Books, 1950)
An abridged version of the adventures of an idealistic country gentleman and his shrewd Squire who set out, like knights of old, to search for adventure and to right wrongs.
Keywords: Knights and knighthood -- Fiction; Spanish literature; Spain -- Fiction